2022
DOI: 10.7150/thno.73400
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Circulating Tumour Cells - complementary liquid biopsies or standalone concepts?

Abstract: Liquid biopsies do promise a lot, but are they keeping it? In the past decade, additional novel biomarkers qualified to be called like that, of which, some took necessary hurdles resulting in FDA approval and clinical use. Some others are since a while around, well known and were once regarded to be a game changer in cancer diagnosis or cancer screening. But, during their clinical use limitations were observed from statistical significance and questions raised regarding their robustness, that eventually led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 220 publications
0
11
0
Order By: Relevance
“…Understanding these mechanisms and precisely following the axis of ncRNA-miR-mRNA is crucial for the future use of exosome inhibitors in cancer therapy. Based on the analyzed research and our observations [ 14 , 30 , 166 , 167 ], it must be noted that both small and large EVs are the future of personalized medicine, including not only in the diagnosis and prognosis of cancer patients but also as a treatment strategy. Such an application of our knowledge of exosomes can rely on two potential activities: (1) inhibiting the release of exosomes [ 168 ] and (2) using exosomes as a platform for chemotherapeutic agent transport [ 169 , 170 ] and as a ‘freighter’ for therapeutic RNAs and peptides [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding these mechanisms and precisely following the axis of ncRNA-miR-mRNA is crucial for the future use of exosome inhibitors in cancer therapy. Based on the analyzed research and our observations [ 14 , 30 , 166 , 167 ], it must be noted that both small and large EVs are the future of personalized medicine, including not only in the diagnosis and prognosis of cancer patients but also as a treatment strategy. Such an application of our knowledge of exosomes can rely on two potential activities: (1) inhibiting the release of exosomes [ 168 ] and (2) using exosomes as a platform for chemotherapeutic agent transport [ 169 , 170 ] and as a ‘freighter’ for therapeutic RNAs and peptides [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review describes the importance of EVs for regulating cancer cell responses to chemotherapy by focusing on the most up-to-date and clinically quintessential relationships between EVs and chemoresistance. As our team, a little while back, noted, most studies have identified the centrality of the role of exosomal ncRNAs in chemoresistance [ 30 ]. Hence, we present here the mechanisms by which these types of EVs modulate the response to cytotoxic drugs by microRNAs (miRNAs, miRs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), all of which have a cardinal role in the regulation of gene expression [ 31 , 32 , 33 ].…”
Section: Prima Facie Of Extracellular Vesicles (Evs) In Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Exosome-based liquid biopsies provide information about the actions of tumor cells and present possible applications for tumor diagnosis, therapeutic response monitoring, and prognosis evaluation [ 55 , 69 ]. Specifically, compared to circulating tumor cells, exosomes give better sensitivity during the initiating process, which is closely linked to carcinogenesis [ 70 ].…”
Section: Potential Exosome-based Strategies In Tumormentioning
confidence: 99%
“…The antigen presentation of exosomes can also serve as a good vehicle for cancer vaccines, providing a new direction for cancer immunotherapy. With the continuous development of medical technology, the diagnostic efficacy of many classical tumor markers is no longer sufficient, 49 and scholars have been searching for biomarkers with higher specificity and sensitivity. Exosomes can be found in blood, urine, cerebrospinal fluid, and even saliva, making it easier to obtain samples for testing.…”
Section: Exosomes Promote Cancer Immune Escapementioning
confidence: 99%